The Experience of University Department in Organizing Research Circles at Schools as a Direction of University Career Guidance Work - E. A. Kogan; D. I. Ponomareva (Высшее образование в России)
Attracting applicants in modern conditions is quite an important and difficult task for higher education institutions. Non-core graduate departments of the University face the greatest difficulties in this process.The article discusses the main directions of career guidance work of the Department of “Sociology, psychology and social management” of the Moscow Aviation Institute (NationalResearchUniversity) in the course of implementing cooperation agreements with educational institutions inMoscowand theMoscowregion. The authors present an experience of organizing and conducting research circles in sociology and social psychology for students of grades 8-11.The activity of the sociological research circle “First steps in science” was aimed at forming students’ ideas about research, its methods and stages; developing skills of independent work with the received social information; obtaining skills for developing, conducting and presenting research results. The program of the circle “Social psychology” adapted for classes of humanitarian and socioeconomic orientation, included personal growth trainings and career guidance games aimed at developing professional self-determination in career planning.Research circles allowed school students to develop their special skills, arouse interest in sociology and psychology, improve their understanding of the criteria for their own professional choice, as well as form students’ understanding of the Department’s profile.During the implementation of career guidance measures in modern conditions, along with positive results, the authors have identified the factors that hinder the successful interaction of schools and universities such as the lack of involvement in this process of all subjects of the educational space, insufficient attention of the school administration to the social needs of graduating departments. To solve these problems, the authors have developed and proposed a model for organizing research circles based on schools, which can qualitatively improve the social partnership of all interested participants. The basic ideas and theses of the article may be of interest both for teachers of higher educational institutions and for pedagogical staff of secondary schools.